Structural Racism in the Federal Workplace: An Intersectional Approach to Examining Race-Based Discrimination in Law Enforcement - Helen H. Yu (Journal of Social Equity and Public Administration, 2023)
Law enforcement has historically been an institution resistant to both women and racial minorities, evident by decades of research on workplace discrimination in local policing. Missing, however, from this research are the workplace experiences of minority officers in federal policing, a growing domain in law enforcement scholarship. This article examines perceived encounters of race-based discrimination and its subsequent outcomes to reporting behavior between White and minority officers. Findings suggest that all minority race or ethnic subgroups except one (e.g., Black/African American, American Indian/Alaska Native, Asian, multi-racial, and Hispanic/Latino officers respectively) were more likely to perceive experiencing race-based discrimination in comparison to White officers, although only three of the minority subgroups (e.g., Black/African American, multiracial, and Hispanic/Latino officers, respectively) were more likely to report the unlawful conduct. Likewise, comparisons between officers of color found that Black/African American women were more likely to perceive experiencing race-based discrimination in comparison to men of color.